Survival and Activity of a 3-Chlorobenzoate-Catabolic Genotype in a Natural System - Fulthorpe, Roberta R. (1989)
A chlorobenzoate-degrading Alcaligenes strain, BR60, was introduced to flowthrough lake microcosms and exposed to 3-chlorobenzoate (3Cba) concentrations from 0 to 25 μM. A DNA probe specific for BR60 chlorobenzoate catabolic genes was used with the most probable number (MPN) technique to enumerate bacteria harboring this genetic information. This MPN-DNA hybridization method combined with [U-(14)C]3Cba uptake rate measurements allowed the correlation of the size and activity of a specific catabolic population in a natural mixed community for the first time. An experiment involving the release of a streptomycin-resistant strain of BR60 indicated that estimates of bacteria carrying the introduced catabolic genotype often outnumbered plate count estimates of viable BR60 by as much as 3 orders of magnitude, particularly when 3Cba inputs were high. The MPN-DNA hybridization method provided catabolic population estimates highly correlated to 3Cba exposure levels and the [U-(14)C]3Cba uptake rates in the microcosms. Plate counts of BR60 were poorly correlated with both 3Cba exposure levels and uptake rates. In the absence of chlorobenzoate selection, the catabolic genotype declined to very low levels by the MPN-DNA hybridization technique after 8 weeks in the microcosms.